ANALYSIS OF ROAD DAMAGE CONDITIONS ON THE SURFACE LAYER USING PCI ( PAVEMENT CONDITION INDEX ) METHOD (CASE STUDY: RASAU JAYA ROAD, KUBU RAYA REGENCY, WEST KALIMANTAN PROVINCE) - Stefanus, Stefanus; Widodo, Slamet; Mukti, Elsa Tri; Erwan, Komala; Azwansyah, Heri (Fakultas Teknik Universitas Tanjungpura, 2022)
The road is an infrastructure in the flow of traffic, the Raya Rasau Jaya section was damaged, with light, medium and heavy damage. One way to determine the condition of road damage is the Pavement Condition Index (PCI) method. The purpose of this study is to determine, identify and calculate the value of road damage that occurs using the PCI method and to know the handling of the road damage. The method used is PCI, the results of field analysis and values calculated by the PCI method, recommendations for road repairs using the Asphal Institute MS-17 method. The results of the analysis of the surface condition of the 8 km road pavement using the PCI method, averaged per 1 Km starting from STA 26+700 to 27+700, 27+700 to 28+700, 32+700 to 33+ 700 classified as good damage, STA 28+700 to 29+700, 29+700 to 30+700, 30+700 to 31+700, 31+700 to 32+700 classified as very good condition, STA 33+700 to 34+700 perfect condition. Recommendations for road repair per 1 Km using the Asphalt institute MS-17 method, namely Routine Maintenance at STA 29+700 to 30+700, 30+700 to 31+700, 31+700 to 32+700, 33 +700 to 34+700 and Patches and Additional Coatings on STA 26+700 to 27+700, 27+700 to 28+700, 28+700 to 29+700, 32+700 s/ d33+700.